2019
DOI: 10.1016/j.ijrobp.2019.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Site SBRT and Sequential Pembrolizumab: Treated Metastasis Control and Immune-Related Expression Predict Outcomes

Abstract: 6.21 vs. 13.3 months, log-rank pZ0.0036; HRZ2.57, pZ0.005) compared to patients with high-RS. High RS values correlated with transcriptional activation of innate and adaptive immune signatures in biopsies from irradiated tumors (nZ35). Conclusions: The RS predicts local irradiated tumor control and OS for patients treated with combined SBRT and pembro. Transcriptional analysis from a subset of patients is concordant with immune activation in high RS tumors. The RS may allow clinicians to utilize imaging at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…A potential approach to minimize SBRT-induced lymphopenia is partial treatment (irradiation of only a portion of the lesion), which has been shown to achieve similar treated metastasis control compared with complete treatment in a prospective trial. 44 Although the patient presented in this case was treated with SBRT, whether a lower dose conventional radiation could have achieved a similar tumor response and control with less severe lymphopenia is unknown. In addition to lymphopenia, thrombocytopenia is a potential side effect associated with splenic irradiation.…”
Section: Discussionmentioning
confidence: 95%
“…A potential approach to minimize SBRT-induced lymphopenia is partial treatment (irradiation of only a portion of the lesion), which has been shown to achieve similar treated metastasis control compared with complete treatment in a prospective trial. 44 Although the patient presented in this case was treated with SBRT, whether a lower dose conventional radiation could have achieved a similar tumor response and control with less severe lymphopenia is unknown. In addition to lymphopenia, thrombocytopenia is a potential side effect associated with splenic irradiation.…”
Section: Discussionmentioning
confidence: 95%
“…We found that local control was similar in complete or SubGTV tumor SBRT treatments. 7 These findings led us to explore whether we could feasibly and safely deliver ultra-high doses of radiation to when they received a BED > 151, a BED between 79 and 151, or a BED < 79, respectively. 9 Taken together, these findings suggest that using even higher BED may be beneficial in treating patients.…”
Section: Discussionmentioning
confidence: 99%
“…The trial implemented a 65 cc treatment volume limit with intent to avoid normal tissue toxicity. 7 Other groups have employed similar partial treatment studies with similar results. 8 While the local control rate approaches 90% at 12 months after treatment with SBRT and immunotherapy, one strategy to continue to improve outcomes and potentially increase the immune response would be to further escalate the SBRT dose.…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, local control was no different between partial tumor radiation coverage (see Figure 2) for larger tumors and smaller ones suggesting a synergistic effect with the immunotherapy. In an exploratory analysis, the only predictor for overall survival was the local control of the irradiated tumor with high dose radiation (47). As oligometastatic states exist between “micrometastatic” and heavily pre-treated metastatic states, evidence from our group further confirms the necessity for local control of large metastatic lesions through cytoreductive SBRT to promote an inflammatory microenvironment and limit immune-exclusion.…”
mentioning
confidence: 99%
“…Another possible mechanism of limiting toxicity adopted by our group has been through decreasing dose to adjacent OARs. In patients receiving immunomodulatory agents, initial observation suggests that local control may be achieved despite significantly decreased doses to the tumor edge (see Figure 2) (46, 47). With this approach, we noticed that the majority of the center of the tumors received a high dose of radiation while the periphery of the tumor received a lower prescription dose.…”
mentioning
confidence: 99%